THE INFLUENCE OF SERVICE QUALITY AND CONSUMER TRUST TOWARDS CUSTOMER SATISFACTION ON SHOPEE IN MANADO - Aldo Lengkong; Maryam Mangantar; Fitty Valdi Arie (Universitas Sam Ratulangi, 2023)
The rapid development of the digital economy in Indonesia has had a positive impact on the national economy, one of which is the growth of various online trading platforms or e-commerce. Shopee is an e-Commerce that serves interactive buying and selling between sellers and buyers online in the form of a mobile application to make it easier for users to carry out online shopping activities without having to open a website through a computer device. The purpose of this study was to the influence of service quality and customer trust towards customer satisfaction on Shopee in Manado. This study uses multiple linear regression. The population in this study is people who shop online through Shopee in Manado. The type of population used in this study is an unlimited population and for the sampling technique using purposive sampling. Keywords: service quality, consumer trust, customer satisfaction